Scenes and Characteristics of Hindostan, Volume 1 With Sketches of Anglo-Indian Society - Roberts, Emma (Cambridge University Press, 1835)
Emma Roberts' 1835 work, compiled from articles she published in the Asiatic Journal, was well received in India and England. Roberts lived in India from 1828 with her sister and her brother-in-law, who served in the 61st Bengal infantry. In 1830 she moved to Calcutta, where she edited and wrote for the Oriental Observer and contributed to periodicals and annuals. Returning to London in 1832, she threw herself into the literary world, publishing in several different fields. This book reveals her sympathetic attitude to the Indian people and her genuine interest in providing a thorough and honest report of their culture. Volume 1 begins with a description of Calcutta. It reflects the diversity of Roberts' interests, covering topics from marriages to murders, domestic arrangements to military operations, religion to shopping, and architecture to dancing. For more information on this author, see http://orlando.cambridge.org/public/svPeople?person_id=robeem
Title from publisher's bibliographic system (viewed on 05 Oct 2015)